Pengaruh Sanksi Perpajakan dan Motivasi Wajib Pajak Terhadap Minat Menggunakan Jasa Konsultan Pajak - Ananda, Sonia; Rambe, Rizki Fillhayati; Arifin, Syamsul Bahri (Journal of Management and Economics Research, 2024)
This study aims to determine the effect of tax sanctions and taxpayer motivation on interest in using tax consultant services. This research was conducted at the Regional Office of DGT SUMUT I. The sampling technique used is random sampling with the calculation of the slovin formula so that 100 taxpayer respondents are obtained. The data analysis technique used is multiple linear regression with the SPSS 26 analysis tool. The results of this study indicate that tax sanctions have no effect on interest in using tax consultant services, while taxpayer motivation affects interest in using tax consultant services.